Unerstanding of ATM (Automated Teller Machine ) in Bangladesh - Hossain, Mosabber; Bari, Razwanul (BRAC University, 2010)
This thesis paper is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering , BRAC University